1 + 1: The Genes for SaleBook - Tatyana Larkina (Journal of Economic Sociology, 2016)
Rene Almeling’s book Sex Cells: The Medical Market for Eggs and Sperm concerns the issues of the gendered framing of the market and the commodification of the human body and its parts. With the rich empirical base of the study, Almeling offers a new way of theorizing bodily commodification, noting the non-commonality of this phenomenon and emphasizing the diversity of market organizational and experienced practices. The detailed and unbiased analysis of market organization and its experience, in which these two aspects are viewed in their interrelationship, promotes a better understanding of what is occurring when bodily products are offered for sale. In addition, Almeling develops Viviana Zelizer’s model for market analysis, adding a biological factor to the economic, structural, and cultural factors. The book teaches us not to forget that the phenomena of the social world are highly complex and multifaceted and, therefore, cannot be explained with the application of simplified analytical schemes. Moreover, Almeling’s study, in which she links together several layers of social reality, is an excellent example of how to deal with this task. The book review acquaints readers with the basic points of the book and sex cells’ market construction in the United States; it also focuses on the issues that require further investigation. The reviewer will try to show the importance of including the biological factor in the theoretical framework for market analyses and its possibilities beyond such a “peripheral” and sensitive subject.